ERiK methodological report III. Conceptualisation and design of the ERiK-surveys 2022 - Schacht, Diana; Gilg, Jakob J.; Gedon, Benjamin; Brusis, Martin; Buchmann, Janette; Drexl, Doris; Hoang, Tony; Jähnert, Alexandra; Kuger, Susanne; Molina Ramirez, Magdalena; Müller, Michael; Preuß, Melina; et al. (2023)
Abstract: The ERiK-Methodological Report III is the third in a series of methodological reports related to the ‘Entwicklung von Rahmenbedingungen in der Kindertagesbetreuung – indikatorengestützte Qualitätsbeobachtung (ERiK)’ study. The report focuses on the conception, sample selection, and survey designs of the ERiK-Surveys 2022. Together with the ERiK-Methodological Report I and II, that cover the ERiK Surveys 2020, it provides comprehensive background information on the ERiK-Surveys conducted in 2022 and describes their progression until December 31, 2021. The subsequent steps, such as implementing the ERiK-Surveys 2022, will be described in a later report. (DIPF/Orig.)